RESPONSIBILITY OF THE FOOD AND DRUG SUPERVISORY AGENCY IN GRANTING LICENSES FOR THE DISTRIBUTION OF FOOD PRODUCTS CONTAINING PIGS SOLD IN MINIMARKETS - Suci Amalia Tirachim, (Budapest International Research and Critics Institute (BIRCI-Journal) : Humanities, 2022)
The Food and Drug Supervisory Agency (BPOM) is an institution that carries out government affairs in the field of drug and food control with the aim of protecting consumers from losses. However, nowadays cases regarding food distribution that harm consumers are still occurring, one of which is food containing pork sold in minimarkets. Where the minimarket sells food products containing pork that are not in accordance with applicable regulations. This study uses a normative juridical legal research method with a law approach and a case approach. Then, using secondary data sources obtained from literature studies, then the data is processed using qualitative analysis. The results of the study show that the Government through BPOM has the responsibility to carry out supervision by providing distribution permits for foods containing pork that have met the standards in accordance with distribution permit regulations, then monitoring minimarkets to ensure food safety is maintained while circulating and taking action if there is food that is contaminated. In circulation does not comply with the applicable provisions as a form of protection for Muslim consumers. Protection of Muslim consumers has been stipulated in Law no. 8 of 1999 concerning Consumer Protection and Law no. 33 of 2014 concerning Halal Product Guarantee. Where business actors are required to meet the applicable requirements in selling food containing pork in minimarkets and provide correct and honest services to consumers in accordance with good retail guidelines. The authors suggest that BPOM can supervise food containing pork sold in Mini Markets more firmly, routinely and thoroughly through cooperation with related parties in order to prevent losses to consumers.